L-Arginine-Modified Silica for Adsorption of Gold(III) - Sri Hastuti; Nuryono Nuryono; Agus Kuncaka (Indonesian Journal of Chemistry, 2015)
In this research, L-arginine-modified silica (SiO2-Arg) with 3-glycidoxypropyl-trimethoxysilane (GPTMS) as the linking agent has been synthesized through sol gel process for adsorption of Au(III) in aqueous solution. Tetraethyl orthosilicate (TEOS) as the silica source precursor, L-arginine solution 0.9 M with various volume ratios and the linking agent were mixed together to form a gel. SiO2-Arg was characterized using Fourier transform infrared (FTIR) spectrophotometer, thermogravimetric analysis (TGA), and an elemental analysis. Adsorption was carried out in a batch system under various experimental conditions including contact time and initial concentration of metal Au(III). The selectivity of adsorbent toward Au(III) was examined in the presence of Cu(II), Fe(III), and Zn(II) ion at various pHs. Results of characterization showed that silica has been successfully modified with L-arginine. The optimum adsorption of Au(III) on SiO2-Arg was obtained at pH of 3.0 and the adsorption isotherm of Au(III) on SiO2-Arg gives the adsorption capacity of 52.79 mg/g. The kinetic study demonstrates that the adsorption of Au(III) ion follows pseudo-second order with the rate constant of 53197 g mol–1 min–1. The selectivity order of Au-Zn = Au-Cu > Au-Fe. This sol-gel preparation is simple and provides prospective application of SiO2-Arg material as an effective adsorbent for metal ions particularly gold(III).